Digital single market conducive to the promotion of social dialogue and social investment in the regional cohesion context - Muravska, Tatjana; Zeibote, Zane; Stacenko, Sergejs (University of Latvia, 2017)
This article examines problems of the digital single market from two perspectives: the extension of a digital economy beyond capital, goods and services to other areas of the economy including labour markets, social dialogue and social dimensions, and from the role of digital government services in regional cohesion perspectives in Latvia. This methodological approach could serve as a tool for integrating a number of main goals related to the Digital Single Market (DSM), that require support of societies as well as the improvement of social welfare at the regional and national levels. This contribution aims to offer insight into the concept of social dialogue (SD) in DSM and the impact of the DSM on regional cohesion. The study observes these implications in relation to the need to expand and adapt the content and approach of the DSM implementation. The further digital development as a precondition for diminishing regional and wellbeing divide in Latvia is discussed. The role of electronic government services and social investment is examined based on the qualitative interviews among users of Unified state and municipal customer service centres (CSC) in Latvia. The article provides recommendations to social partners for DSM regulatory system of decision-making as well as social investment for improving social welfare at regional and national levels. It is concluded that the digitalization and implementation of SDM have inevitably become more important due to the increased digital competitiveness of countries.
This research paper has been supported by the European Union's Horizon-2020 research and innovation programme under the Grant agreement 726755.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; digital single market; social dialogue; social investment; regional cohesion; digital government services